PECULIARITIES OF USING DIGITAL TECHNOLOGIES IN PHYSICS LESSONS IN VOCATIONAL EDUCATION INSTITUTIONS (Innovative professional education, 2025)
The article examines the features of using digital technologies in teaching physics in vocational education institutions. The main advantages of applying interactive resources, virtual laboratories, simulations, 3D modeling, augmented and virtual reality in the learning process are analyzed. The role of digital technologies in improving the visualization of physical processes, enhancing the practical component of education, personalizing the educational process, and motivating students is determined. Specific examples of effective use of digital tools that contribute to the development of critical thinking, research skills, and the integration of theoretical knowledge with practice are provided.
Keywords: digital technologies, physics, vocational education, virtual laboratories, simulations, 3D modeling, augmented reality, personalized learning, interactive learning